Modelling and simulation of hydrogenation of dimethyl oxalate in ethylene glycol production. Issue 1 (December 2020) - Rohman, F S; Sulaiman, S H S; Aziz, N
Abstract: In this work, the production of ethylene glycol was studied through a syngas-derived ethylene glycol route known as the indirect syngas-to-ethylene glycol process via oxalates. The improvement of hydrogenation of dimethyl oxalate process is pivotal in production of ethylene glycol. Therefore, it is noteworthy to analyse the effect of certain operating parameters on the reactor's performance. Simulation analysis is an effective approach that allows to study the effect of hydrogen to dimethyl oxalate mole ratio (HDMR), Methyl Glycolate to Dimethyl Oxalate Mole Ratio (MDMR) and temperature on the conversion and selectivity of ethylene glycol. The kinetic of hydrogenation reaction in gas phase in the presence of catalyst was developed in Langmuir-Hinshelwood and Hougen-Watson form. A process model within plug flow reactor was developed using the RPLUG in Aspen Plus V10 simulator. The simulation data from literature was used to validate the model. The error obtained in validation for main product (ethylene) and by-product (methanol) found were below 10% which was acceptable. From the simulation, the reactor temperature and HDMR have significant effects on the conversion of dimethyl oxalate and yield of ethylene glycol. On the other hand, MDMR has little influence on the responding variable.